Synthesis and Characterization of AIE-Active B–N-Coordinated Phenalene Complexes - Fu, Yubin; Liu, Junzhi; Wu, Zhongbin; Weigand, Jan J.; Feng, Xinliang (Organic Materials, 2020)
Organoboron compounds provide a new line to tune the electronic structures of π-conjugated molecules, which is critical to the development of new organic semiconductor materials. In this work, we demonstrate the synthesis of two novel boron–nitrogen (B−N) coordinated phenalene complexes (BNP-PX and BNP-PA) by employing BN phenalene (BNP) as the acceptor unit and phenoxazine/phenylphenazine groups as the donors. Based on single-crystal X-ray analysis, both BNP-PX and BNP-PA possess highly twisted conformations with the dihedral angles of 76.6 ° and 70.5 °, respectively. The photophysical properties of BNP-PX and BNP-PA are elucidated through UV-vis absorption, fluorescence spectroscopy, and theoretical calculations. In addition, BNP-PX exhibits a large Stokes shift (8,033 cm−1) and excellent aggregated-induced emission behavior. The red organic light-emitting diode device was fabricated based on compound BNP-PX, manifesting its promising application in organic optoelectronic devices.
Keywords: donor–acceptor; BN-coordinated compounds; large Stokes shift; AIE effect; OLED device